Game Anti Narkoba Berbasis multi-platform - Mufa'adhi, Aziz, Endah Sudarmillah S.T, M.Eng (2016)
Drugs have a devastating impact for our young generation. Prevention and eradication of drug abuse should be taken to protect the nation's future. The introduction of the harmful effects of drug abuse through the game as a means of socialization to reduce the number of drug abuse. In the creation of the game is about the adverse effects of drugs. This game is made by the method of SDLC (System Development Life Cycle) is lowered to the stage sequentially system begins with a storyboard game, then implemented with supporting software to create gaming applications. Based on the results of black box testing and testing of potential users is done by asking respondents tto try out a game created and then fill out a questionnaire 96,6% respondents agree that the game is going well. This game aims to introduce harm and keep person to abuse or use drugs. This game can be operated on software, android and a computer, so it can afford to be multi-platform.